The knowledge, attitude and practice of infant allergy prevention among breastfeeding peer counselor in Pahang - Mahasan, Ainun Syuhada; Mohd Shukri, Nor Azwani; Abdul Ghani, Radiah (2019)
It is estimated that 30 to 40% of children in Malaysia have allergies that also involved breastfed infants. Maternal diet during pregnancy and breastfeeding was found to be one of the factors that may lead to allergy reaction in infants. The increasing trends of allergy among infants leads to the question whether mothers have a sufficient knowledge. One of the sources of information is via breastfeeding peer counselor. Objective: This study aimed to identify knowledge, attitude and practice (KAP) of breastfeeding, maternal diet and infant allergy prevention among Breastfeeding Peer Counselor (BPC) in Pahang.